Pengaruh Program Samsat Keliling, E-Samsat dan Kesadaran Dalam Membayar Pajak Terhadap Penerimaan Pajak Kendaraan Bermotor Pada UPTD Pendapatan Daerah di Wilayah Kota Kupang (Kantor Samsat Kota Kupang) - Irmawati Handayani Wahid; Anthon S. Y. Kerihi; Maria P. L. Muga (Kajian Ekonomi dan Akuntansi Terapan, 2024)
This study aims to determine the effect of the Mobile SAMSAT program, E-SAMSAT and awareness in paying taxes on motor vehicle tax revenues at the Kupang City Regional Revenue UPTD or the Kupang City SAMSAT Office. This study uses a descriptive statistical approach. The population in this study were all taxpayers registered at the Kupang City Regional Revenue UPTD. The sampling technique and determination of informants in this study used purposive sampling. The number of samples in this study was 100 respondents and the data collection method was carried out by distributing questionnaires. Data analysis used in this study was validity testing, reliability testing, classical assumption testing, multiple linear regression and hypothesis testing using IBM SPSS Statistics 26. The results of simultaneous testing showed that the variables of the Mobile SAMSAT program, E-SAMSAT and awareness in paying taxes had a significant effect on increasing motor vehicle tax revenues in Kupang City. The Mobile SAMSAT and E-SAMSAT programs supported by increased taxpayer awareness will have a positive effect on increasing Motor Vehicle Tax revenues because they simplify the payment process and increase the fulfillment of motor vehicle taxpayers in Kupang City.